2010
DOI: 10.1002/jhm.574
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis

Abstract: Acute pancreatitis is a common disease most frequently caused by gallstone disease or excess alcohol ingestion. Diagnosis is usually based on characteristic symptoms, often in conjunction with elevated serum pancreatic enzymes. Imaging is not always necessary, but may be performed for many reasons, such as to confirm a diagnosis of pancreatitis, rule out other causes of abdominal pain, elucidate the cause of pancreatitis, or to evaluate for complications such as necrosis or pseudocysts. Though the majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 92 publications
0
38
0
Order By: Relevance
“…10 Mild acute pancreatitis presents with minimal organ dysfunction and an uneventful recovery while severe acute pancreatitis is associated with local and systemic complications and higher mortality, thus it is important to identify patients having severe disease. 7 Categorization of patients based on the type of pancreatitis was made in this study by using ultrasonography which showed 12% cases of chronic pancreatitis, 76% cases of acute pancreatitis and 12% cases of acute on chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10 Mild acute pancreatitis presents with minimal organ dysfunction and an uneventful recovery while severe acute pancreatitis is associated with local and systemic complications and higher mortality, thus it is important to identify patients having severe disease. 7 Categorization of patients based on the type of pancreatitis was made in this study by using ultrasonography which showed 12% cases of chronic pancreatitis, 76% cases of acute pancreatitis and 12% cases of acute on chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 97%
“…1,7,8 It is a complex process which varies from mild self-limiting inflammation to rapidly deteriorating condition which poses a serious threat to life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients should be placed on bowel rest, receive nothing by mouth and undergo aggressive fluid resuscitation due to third space losses 87 . Adequate pain control is essential, often through the use of opioid narcotics [88][89][90] . Some controversy still remains about the potential for medication-induced sphincter of Oddi dysfunction aggravating the clinical picture although low dose transdermal fentanyl patches appear do not to compromise sphincteric function 91,92 .…”
Section: Treatmentmentioning
confidence: 99%
“…In adults, the most common causes of AP are alcohol and gallstones, 9,10 but in children it is associated with a wide variety of potential aetiologies, including abdominal trauma, drug therapy, infections, systemic diseases and congenital anatomical anomalies. 2,11 Trauma and mumps were the commonest associations reported in the UK in the 1970/80's.…”
Section: Introductionmentioning
confidence: 99%